A Decision Support System Based on The Weighted Sum Model for Determining Priority of Service Improvements in The Travoy Application - Muhammad Rifai, Asep; Meutia Hilda, Atiqah (ARRUS Journal of Engineering and Technology, 2024)
Customer service is an aspect that needs to be evaluated regularly as it is one of the company's efforts to maintain its business performance. PT Jasa Marga (Persero) Tbk, which operates the Travoy application as a digital platform to provide public information services to road users, has faced a decline in the public information service satisfaction index from 4.74 to 4.60. This decline is a serious concern for the company because service to road users is part of the company's mission. Therefore, a study was conducted to identify and analyze the problems in the Travoy application and to determine the priorities for service improvement. The method used in the development of the Decision Support System (DSS) is the Weighted Sum Model (WSM). The results of the implementation of the WSM-based Decision Support System indicated that the priority for improving the Travoy application service is enhancing the application's stability with a total score of 8.37.